Hemodynamics and Tissue Temperature in Bone Union Area of Long Bones Primary Fractures and Refractures: in vivo Experiment - Azam A. Kosimov; Iskandar Yu. Khodzhanov; Natalia A. Kononovich (Travmatologiâ i Ortopediâ Rossii, 2022)
Background. Adequate blood flow in tissues during bone union is a factor that enables to achieve positive treatment results.